RCM-PMBOK HYBRID METHODOLOGY FOR MANAGING THE MAINTENANCE OF CRITICAL BIOMEDICAL EQUIPMENT IN IPS OF MEDIUM COMPLEXITY - Duque Suarez, Oscar Manuel; Lucas Mármol , Antonio; Gomez Camperos, July Andrea (Journal of Applied Engineering Science, 2023)
The research carried out resulted in the proposal to create a hybrid methodology between two topics such as RCM and PMBOK applied to the management of critical equipment maintenance in the biomedical area in health service providers (IPS) of medium complexity of the city of Cúcuta, Colombia. The hybrid methodology is based on a five-phase project structure, with overall management and tactical activities, deliverable documents for biomedical maintenance management (GMB) and more for GMB activity documentation, recommended tools and techniques for the implementation of activities, in addition to recommended guidelines and formats, where this was applied directly in four medium complexity Health Service Providers (IPS) Institutions of Cúcuta-Colombia, in which product of the professional and teaching experience of the author of this research with the design and execution of maintenance plans based on reliability for these institutions, are considered as case studies since they have the design basis of the RCM in three of them and the fourth is presented as a pilot where the hybrid model to be designed was implemented from scratch.